Inhibition of chlorophyll biosynthesis at the protochlorophyllide reduction step results in the parallel depletion of Photosystem I and Photosystem II in the cyanobacterium Synechocystis PCC 6803 - Kopečná, Jana; Sobotka, Roman; Komenda, Josef (Planta, 2013)
In most oxygenic phototrophs, including cyanobacteria, two independent enzymes catalyze the reduction of protochlorophyllide to chlorophyllide, which is the penultimate step in chlorophyll (Chl) biosynthesis. One is light-dependent NADPH:protochlorophyllide oxidoreductase (LPOR) and the second type is dark-operative protochlorophyllide oxidoreductase (DPOR). To clarify the roles of both enzymes, we assessed synthesis and accumulation of Chl-binding proteins in mutants of cyanobacterium Synechocystis PCC 6803 that either completely lack LPOR or possess low levels of the active enzyme due to its ectopic regulatable expression. The LPOR-less mutant grew photoautotrophically in moderate light and contained a maximum of 20 % of the wild-type (WT) Chl level. Both Photosystem II (PSII) and Photosystem I (PSI) were reduced to the same degree. Accumulation of PSII was mostly limited by the synthesis of antennae CP43 and especially CP47 as indicated by the accumulation of reaction center assembly complexes. The phenotype of the LPOR-less mutant was comparable to the strain lacking DPOR that also contained <25 % of the wild-type level of PSII and PSI when cultivated under light-activated heterotrophic growth conditions. However, in the latter case, we detected no reaction center assembly complexes, indicating that synthesis was almost completely inhibited for all Chl-proteins, including the D1 and D2 proteins.
Keywords: Protein Binding; Synechocystis; fenotyp; protochlorofylid; Phenotype; Enzyme Activation; Photosystem I Protein Complex; Bacterial Proteins; 2D gelová elektroforéza; Gene Expression Regulation, Enzymologic; Chlorophyll; Electrophoresis, Gel, Two-Dimensional; transformace genetická; Protochlorophyllide; fotosystém I (proteinový komplex); elektroforéza v polyakrylamidovém gelu; regulace genové exprese u rostlin; Oxidoreductases Acting on CH-CH Group Donors; světlo; Transformation, Genetic; chlorofyl; vazba proteinů; Cell Membrane; Electrophoresis, Polyacrylamide Gel; fototrofní procesy; Gene Expression Regulation, Plant; regulace genové exprese enzymů; oxidoreduktasy působící na CH-CH vazby; buněčná membrána; Phototrophic Processes; bakteriální proteiny; Photosystem II Protein Complex; aktivace enzymů; Light; fotosystém II (proteinový komplex)